2021
DOI: 10.1111/1750-3841.15868
|View full text |Cite
|
Sign up to set email alerts
|

Antrocaryon amazonicum: An unexploited Amazonian fruit with high potential of scavenging reactive oxygen and nitrogen species

Abstract: Antrocaryon amazonicum fruits are unexploited sources of bioactive compounds found in the Amazonia region of Brazil. In this study, for the first time, the carotenoid and phenolic compound profiles of the pulp and peel of A. amazonicum fruits, from two varieties at two harvest periods, were determined by LC-MS. Additionally, the potential of the peel and pulp extracts to scavenge physiologically relevant reactive oxygen species (ROS) and reactive nitrogen species (RNS) was assessed. The major carotenoids in bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The ethanol–water extract of A. chica leaves showed that the total phenolic compound contents were ≈10 times lower than that found in the hydromethanolic extract of the same plant (21.5 mg/g) [ 20 ]. By comparing extracts obtained from other vegetables, it showed lower values than the hydroalcoholic extract of artichoke leaves ( Cynara cardunculus ) (73 mg/g), similar to Eryngium foetidum (9.99 mg/g) [ 40 ] and higher than extracts obtained from the peel (5.4 mg/g) and pulp (1.8 mg/g) of Antrocaryon amazonicum fruits [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ethanol–water extract of A. chica leaves showed that the total phenolic compound contents were ≈10 times lower than that found in the hydromethanolic extract of the same plant (21.5 mg/g) [ 20 ]. By comparing extracts obtained from other vegetables, it showed lower values than the hydroalcoholic extract of artichoke leaves ( Cynara cardunculus ) (73 mg/g), similar to Eryngium foetidum (9.99 mg/g) [ 40 ] and higher than extracts obtained from the peel (5.4 mg/g) and pulp (1.8 mg/g) of Antrocaryon amazonicum fruits [ 41 ].…”
Section: Resultsmentioning
confidence: 99%